2014
DOI: 10.1590/s1415-43662014000500005
|View full text |Cite
|
Sign up to set email alerts
|

Initial physic nut nutrition and potassium balance in the soil-plant system

Abstract: A B S T R A C TThe objectives of this study were to evaluate the mineral nutrition and the response of physic nut to potassium fertilization as well as to assess whether the species can absorb K from the non-exchangeable soil fraction. The study was conducted in a greenhouse, in randomized blocks, and with four repetitions. Physic nut plants were cultivated in plastic recipients filled with 50 dm 3 of a Dark Red Latosol fertilized with rates of 0, 40, 80, 120 and 160 mg K dm -3 of soil. One hundred and fifty d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Clark et al (1997) observed a calcium concentration reduction in maize shoot with an increasing application of magnesium, while potassium remained constant. Freiberger et al (2014) reported an inhibitory effect of potassium on magnesium absorption in jatropha plants.…”
Section: Resultsmentioning
confidence: 99%
“…Clark et al (1997) observed a calcium concentration reduction in maize shoot with an increasing application of magnesium, while potassium remained constant. Freiberger et al (2014) reported an inhibitory effect of potassium on magnesium absorption in jatropha plants.…”
Section: Resultsmentioning
confidence: 99%